Perbandingan Teknik Relaksasi Otot Progresif dan Akupresur Terhadap Dismenore Pada Mahasiswi FKP Universitas Riau - Cica Kristina; Oswati Hasanah; Ririn Muthia Zukhra (HEALTH CARE : JURNAL KESEHATAN, 2021)
Dysmenorrhea is a normal condition for some women who experience menstruation, asa result of the hormone progesterone imbalance in the blood that causes contractions between the tonus miometrium and the uterus to produce ischemia, bleeding and pain. The purpose of this study is to analyze acupuncture therapy more effective than the progressive muscle relaxation of dysmenorrhea pain in students' FKP at Riau University with the principle of district and relaxation using the scale measuring measuring factor. The study used the design quasy expo with the two groups pre-post design test. The study sample is that of a student who was diagnosed with a dismenorrhea of 38 people who split into two groups, a progressive muscle relaxation group and an acupressure sampling. The data analysis Uses the wilcoxon test and mann Whitney. Studies show acupressure therapy and progressive muscle relaxation can lower the intensity of pain by p-value 0.001 < α (0.05). The conclusion of the study is that acupuncture therapy reduces the intensity of dysmenrhea pain more than progressive muscle relaxation.